2019
DOI: 10.1140/epjb/e2019-100306-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optical, electrical and optoelectronic properties of SnSe crystals

Abstract: The optical, electrical and optoelectronic properties of tin selenide crystals are of immense significance for application in photodetectors and energy conversion and storage devices. The transition metal chalcogenides possess a layered structure that interacts with each other through van der Waal forces and can also offer sites for intercalation. The low molecular weight materials like GeSe and SnSe are found in an orthorhombic structure. In this article, the optical, electrical and optoelectronic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 55 publications
(50 reference statements)
0
32
0
Order By: Relevance
“…In contrast, the devices with ultrafast response speed ≈µs, has graphene as transparency electrode, to greatly facilitate the carrier collection and reduce carrier recombination. [ 7a,15–17,43 ] Moreover, the single cycle I–t curve of the device at 0 V is illustrated in the Figure S9 (Supporting Information), indicating τ r = 1.256 s and τ f = 336 ms, respectively. The device exhibits a comparatively longer response and recovery time under zero bias, attributed to the relatively small built‐in electrical field.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the devices with ultrafast response speed ≈µs, has graphene as transparency electrode, to greatly facilitate the carrier collection and reduce carrier recombination. [ 7a,15–17,43 ] Moreover, the single cycle I–t curve of the device at 0 V is illustrated in the Figure S9 (Supporting Information), indicating τ r = 1.256 s and τ f = 336 ms, respectively. The device exhibits a comparatively longer response and recovery time under zero bias, attributed to the relatively small built‐in electrical field.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the excellent electronic and optical properties of binary compounds in transition metals, many scholars have conducted in-depth research in photovoltaic and solar-cell systems. [1][2][3][4][5] Among binary compounds in transition metals, SnSe has great application prospects because SnSe has an orthorhombic crystal structure, 6 which is suitable for solar cells. SnSe is a p-type semiconductor and its high absorption coefficient (10 5 cm À1 ) ensures that solar radiation is absorbed almost completely.…”
Section: Introductionmentioning
confidence: 99%
“…Shiny grey crystals and powder were collected after the growth process. 11,14,22 The thin-film-based metal and semiconductor materials were deposited on a glass substrate using the thermal evaporation technique using a Hind-High Vacuum coating unit (Model No. 12A4D).…”
Section: Methodsmentioning
confidence: 99%
“…its real stoichiometry varies with temperature. 11 A previous report suggests that SnSe exhibits a p-type nature determined from the Hall effect measurement. 12 Considerable studies have been reported on the deposition of tin selenide thin films, performed using several deposition techniques such as chemical vapour deposition, 13 thermal evaporation techniques, 14 chemical bath deposition, 15 electrodeposition 16 and electrophoresis.…”
Section: Introductionmentioning
confidence: 97%